Separable Preferences over Intertemporal Opportunities - LAHIRI, Somdeb (Journal of Mathematical Economics and Finance, 2016)
In this paper, we provide an axiomatic characterization of separable preferences, over intertemporal opportunities, satisfying “existences of a dummy alternative”. The two properties of preferences over intertemporal opportunities, that implies and is implied by sep- arability, are the following: (i) if for some opportunity set A, one alternative chosen along with A is at least as good as another, then the same relation holds for the pair of alternatives, when they are chosen with any other opportunity set; (ii) if one intertemporal opportunity is at least as good as another, when chosen with a given alternative, and if “one alternative along with the default opportunity set” is at least as good as “another alternative with the default opportunity set”, then the first alternative with the first opportunity set is at least as good as the second alternative together with the second opportunity set.